Population in urban development and the practical problems of urban planning policy in Africa - Joseph Uyanga (Faculty of Geography, Universitas Gadjah Mada, 1986)
The paper analyses the pattern of recent growth in African towns, examines the population component in this growth process and discusses the attendant urban planning problems. The contention in the study is that there are problems of definition. policy enunciation, and organisational co-ordination in the conceptualization. planning. orchestration and implementation of urban development and service systems. The magnitude of African urban developmental problems, and its multi-faceted nature demands that the latest in scientific knowledge and technological innovations should be integrated and incorporated into the urban planning and implementation processes.